2006
DOI: 10.1093/ps/85.7.1200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary phosphorus, phytase, and 25-hydroxycholecalciferol on broiler chicken bone mineralization, litter phosphorus, and processing yields

Abstract: Three floor pen experiments (Exp) were conducted to evaluate low nonphytin P (NPP) concentrations and the NPP sparing effect of phytase (PHY) and 25-hydroxycholecalciferol (25D) on bone mineralization, bone breaking during commercial processing, litter P, and water-soluble P (WSP) concentrations. Tested treatments (TRT) were control, National Research Council NPP; University of Maryland (UMD) NPP; UMD + PHY, UMD NPP reduced by 0.064% NPP + 600 U of PHY/kg; UMD + PHY + 25D, UMD NPP reduced by 0.090% NPP + 600 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
33
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 28 publications
7
33
1
4
Order By: Relevance
“…The carcass yield obtained in the present trial did not differ from a previous study (Angel et al, 2006) using different dietary P levels of P and supplemental vitamin D sources, including the 25-hydroxycholecalciferol. Brito et al (2010) obtained higher carcass yield (p<0.05) with the dietary addition of 25-hydroxycholecalciferol compared with cholecalciferol.…”
Section: Resultscontrasting
confidence: 51%
“…The carcass yield obtained in the present trial did not differ from a previous study (Angel et al, 2006) using different dietary P levels of P and supplemental vitamin D sources, including the 25-hydroxycholecalciferol. Brito et al (2010) obtained higher carcass yield (p<0.05) with the dietary addition of 25-hydroxycholecalciferol compared with cholecalciferol.…”
Section: Resultscontrasting
confidence: 51%
“…Esses resultados corroboram aqueles observados por Korver (2005), porĂ©m, diferem dos encontrados por Angel et al (2006). O estudo sobre os efeitos de diferentes fontes de vitamina D sobre caracterĂ­sticas de carcaça ganhou força nos Ășltimos anos e hĂĄ relatos de redução nas perdas e de condenaçÔes das carcaças nos abatedouros, em decorrĂȘncia da melhoria na qualidade ou densidade Ăłssea.…”
Section: Resultsunclassified
“…However, in literature, phytase nutritional matrix results were not considered in the formulation of the experimental diets, and therefore Using low available phosphorus levels and phytase inclusion, Persia & Saylor (2006) showed that phytase improved the performance of 8-to 22-day-old broilers, as opposed to Angel et al (2006), who did not find any broiler performance differences during the starter phase when adding phytase to low available phosphorus diets. Table 5 shows performance parameter means for the phase of 22-42 days of age.…”
Section: Resultsmentioning
confidence: 99%